BENTUK EKSPLISIT RUMUS BEDA MAJU DAN BEDA MUNDUR UNTUK TURUNAN KE-N DENGAN ORDE KETELITIAN KE-N BERDASARKAN DERET TAYLOR - Ikhsan Fachriansyah Putra; Mahdhivan Syafwan; Monika Rianti Helmi; Admi Nazra (LPPM Universitas Bina Bangsa, 2023)
In this paper, we aim to derive the explicit forms of forward and backward difference formulas based on the Taylor series. These formulas are employed to approximate the N-th derivative of a single-variable function with N-th order accuracy. The explicit formula is determined by utilizing the properties of the determinant of the Vandermonde matrix. Subsequently, we apply the obtained formulas to an example case involving a first-order ordinary differential equation